Analisis Kandungan Logam Berat Timbal (Pb) dan Cadmium (Cd) pada Kerang Hijau (Perna viridis L.) di Perairan Ngemboh Kabupaten Gresik Jawa Timur [ Analysis Of Heavy Metal Content Of Lead (Pb) And Cadmium (Cd) Shells On Green (Perna viridis L.) On Water District Ngemboh Gresik East Java] - Gunanti Mahasri; M Ervany Eshmat; Boedi Setya Rahardja (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Ngemboh waters is an important area for fishing around for a long time been used as area fisheries, but the development of industrial waste and household waste in the area led to environmental pollution. The potential of green mussels in Gresik particularly very abundant Ngemboh. The production of green mussels in Gresik particularly very abundant Ngemboh. The production of green mussel fishing village Ngemboh which in 2011 was 3052.89 tons, in 2012 the village catch Ngemboh 1223.46 tons (Department of Fisheries and Marine Gresik, 2013). In 2012 the production of green mussel expected to decline in the presence of the oil leak on PT X (Sugiyono, 2012). Research with the title of the analysis of heavy metals lead (Pb) and cadmium (Cd) in green mussels (Perna viridis L.) in the waters Ngemboh Gresik in East Java will be held in the waters Ngemboh in July 2013. Green mussel (Perna viridis) is one type of shellfish that is popular with the public, has a value economically, and nutrients that are very good to eat, which is composed of 40% water, 21.9% protein, 14.5% fat, 18.5 % carbohydrate, and 4.3% ash. Lead is a non-essential metal that is present in nature as a result of natural processes and human activities such as mining, burning coal, cement plants, and is used in gasoline (Mulyanto, et al. 1993). Furthermore, Pb may be mentioned that in the natural water bodies and the impact of human activity. Cadmium in to the various types of mining waste mixed metal such as cadmium, lead, mixing industrial metal, Zn purification, and pesticides.